2016
DOI: 10.6018/analesbio.38.07
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and osteological malformations in hatchery bred redline torpedo fish, Sahyadria denisonii (Day 1865) (Cyprinidae)

Abstract: Malformaciones morfológicas y oseas en ejemplares de criadero de barbo de línea roja, Sahyadria denisonii (Day 1865) (Cyprinidae)Se publican, por primera vez, malformaciones morfológicas y osteológicos de Sahyadria denisonii producidas en criadero. Se fotografiaron anomalías morfológicas con cámara digital y de rayos X digital. De 950 larvas producidas, sólo 12 individuos (1,26 %) presentaron algún tipo de anomalía, incluyendo lordosis, escoliosis, cifosis, semi-opérculo, deformidad de la aleta, deformidad de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The deformity of larvae was highest in the H-3 hatchery which might be due to fertilization of poor egg, adverse impact of some factors during breeding period like inbreeding, insufficiency of nutrients, disease, oxygen reduction, water current, sudden changes in temperature etc. which was similar to the deformities reported by Sahoo et al [15,16] and Sanjeevan [17] . They reported that deformities of larvae is due to the impact of several unfavorable biotic and abiotic factors during hatchery operation.…”
Section: Resultssupporting
confidence: 91%
“…The deformity of larvae was highest in the H-3 hatchery which might be due to fertilization of poor egg, adverse impact of some factors during breeding period like inbreeding, insufficiency of nutrients, disease, oxygen reduction, water current, sudden changes in temperature etc. which was similar to the deformities reported by Sahoo et al [15,16] and Sanjeevan [17] . They reported that deformities of larvae is due to the impact of several unfavorable biotic and abiotic factors during hatchery operation.…”
Section: Resultssupporting
confidence: 91%
“…Operculum complex and caudal fin complex were the most influenced structures. In gilthead seabream and many other species, operculum complex deformities are frequent [ 9 , 29 , 30 , 31 , 32 ]. The frequency of opercular anomalies on Ctrl groups (9.7 and 21.3%) was in the range of 6.3 to 43.2% as registered in previous studies conducted over the past two decades [ 9 , 30 ].…”
Section: Discussionmentioning
confidence: 99%